2016
DOI: 10.1371/journal.pone.0147624
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel er1 Allele Conferring Powdery Mildew Resistance in Chinese Pea (Pisum sativum L.) Landraces

Abstract: Pea powdery mildew, caused by Erysiphe pisi D.C., is an important disease worldwide. Deployment of resistant varieties is the main way to control this disease. This study aimed to screen Chinese pea (Pisum sativum L.) landraces resistant to E. pisi, and to characterize the resistance gene(s) at the er1 locus in the resistant landraces, and to develop functional marker(s) specific to the novel er1 allele. The 322 landraces showed different resistance levels. Among them, 12 (3.73%), 4 (1.24%) and 17 (5.28%) land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 49 publications
0
61
0
Order By: Relevance
“…This mutation differed from all known er1 alleles, indicating that the E. pisi resistance of G0004389 was controlled by a novel allele of er1 . This novel allele was designated er1 -8, following the accepted nomenclature [14,26,27,42,44,51]. In pea germplasm G0004400, a 1-bp deletion (T) was identified in a previously unreported position homologous to position 928 in exon 10 of the PsMLO1 cDNA sequence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This mutation differed from all known er1 alleles, indicating that the E. pisi resistance of G0004389 was controlled by a novel allele of er1 . This novel allele was designated er1 -8, following the accepted nomenclature [14,26,27,42,44,51]. In pea germplasm G0004400, a 1-bp deletion (T) was identified in a previously unreported position homologous to position 928 in exon 10 of the PsMLO1 cDNA sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Their results have indicated that resistance to E. pisi is controlled by two single recessive genes ( er1 and er2 ) and one dominant gene ( Er3 ) [11,12,13,14]. The er1 , er2 , and Er3 genes have been mapped using linked markers [15,16,17,18,19,20,21,22,23,24,25,26,27]. The genes er1 and er2 map to pea linkage groups (LGs) VI and III, respectively [17,28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations